2012
DOI: 10.1111/j.2047-2927.2012.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm retrieval and live birth rates in presumed Sertoli‐cell‐only syndrome in testis biopsy: a single centre experience

Abstract: SUMMARYWe aimed to investigate sperm retrieval rates (SRR) by testicular sperm extraction (TESE), factors affecting SRR, and fertilization rate (FR), implantation rate (IR), clinical pregnancy rate (CPR) and live birth rate (LBR) in patients with presumed Sertoli-cell-only syndrome in testis biopsy (SCOS). We retrospectively evaluated files of 134 patients with SCOS who underwent TESE. Group I were patients in whom spermatozoa were retrieved and Group II were patients in whom no spermatozoa could be retrieved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
(32 reference statements)
3
12
1
1
Order By: Relevance
“…We observed that once sperm was successfully obtained, spermatozoa from patients in the three subgroups (HS, MA, and SCO) did not yield significantly different laboratory results. These results agree with those of other reports [Abdel Raheem et al 2013;Gul et al 2013]. However, other studies have reported lower fertilization rates using spermatozoa obtained from men with MA vs. HS, as well as other differences using spermatozoa from men with MA vs. SCO, although these differences were not significant.…”
Section: Discussionsupporting
confidence: 45%
“…We observed that once sperm was successfully obtained, spermatozoa from patients in the three subgroups (HS, MA, and SCO) did not yield significantly different laboratory results. These results agree with those of other reports [Abdel Raheem et al 2013;Gul et al 2013]. However, other studies have reported lower fertilization rates using spermatozoa obtained from men with MA vs. HS, as well as other differences using spermatozoa from men with MA vs. SCO, although these differences were not significant.…”
Section: Discussionsupporting
confidence: 45%
“…There is lack of study so far evaluating the impact of clinical and hormonal variables on SRR, PR and LBR in each common testicular histological subsets of NOA, separately. Only a recent study investigated the role of age, infertility period, FSH levels and testosterone levels on SRR, PR and LBR in only SCO group of NOA and they found none of these factors have an impact on the TESE and ICSI outcomes in SCO (Gul et al ., ). Similarly, in our study, there was no statistically significant relation between these variables and SRR, motile SRR and PR in this testicular histology, particularly.…”
Section: Discussionmentioning
confidence: 97%
“…For example, SCOS patients and men with KS have shown SSRs around 30%. 13,18 This data not only delineates the etiology of azoospermia among a large group of men, it also allows early prognostic information on initial evaluation of azoospermic men. This is vital in reassuring the patient that a cause and treatment for the condition can often be identified.…”
Section: Edo Was Reported Bymentioning
confidence: 96%
“…[12][13][14][15][16] Historically, testicular biopsy was used to predict the success of SSR. 17 However, this procedure in a diagnostic setting only is now thought to be invasive and unnecessary, and may even hamper success rates for later SSR.…”
Section: Edo Was Reported Bymentioning
confidence: 99%